The importance of environmental threats and ideology in explaining extreme self-sacrifice. (27th December 2018) - Elnakouri, Abdo; McGregor, Ian; Grossmann, Igor
Abstract: We argue that Whitehouse's group-based model neglects two key contextual variables: environmental threats and ideology. Environmental threats lead to extremism outside of group settings and predispose individuals toward joining ideologically zealous groups. Ideologies and environmental threats can also explain why certain groups adopt norms that encourage violent self-sacrifice.